Penerapan Norma Akad Mudharabah Dalam Proses Profit And Loss Sharing - Ajeung Syilva Syara Noor Silmi Sudrajat; Sinta Rusmalinda; Akfah Zakiah Jamilah (STAI Al-Mas'udiyah, 2022)
The profit sharing system or Profit Loss Sharing (LPS) in musyarakah and mudharabah contracts was initially considered the backbone of the operation of Islamic Financial Institutions (LKS), but in practice, this type of profit sharing financing is only a small part of what LKS provides in Indonesia. In this discussion, the application of the mudharabah contract in Profit and Loss Sharing will be discussed. The results show that the profit and loss sharing system in its implementation is a form of cooperation agreement between investors (investors) and capital managers (entrepreneurs) in carrying out economic business activities, where both of them will be bound by a contract that in the business if profits will be shared both parties according to the ratio agreed at the beginning of the agreement, and similarly if the business suffers a loss, it will be borne together according to their respective portions.